2018
DOI: 10.30868/im.v1i2.277
|View full text |Cite
|
Sign up to set email alerts
|

Kepemimpinan Kepala Sekolah Dan Pengaruhnya Terhadap Peningkatan Pedagogik Guru Pendidikan Agama Islam Di SMP Negeri 3 Karawang Jawa Barat

Abstract: AbstrakPenelitian ini bertujuan untuk menganalisis kepemimpinan kepala sekolah terhadap peningkatan kompetensi pedagogik guru pendidikan agama Islam (PAI). Kompetensi pedagogik adalah salah satu dari empat kompetensi yang harus dimiliki oleh guru untuk dapat memahami indikator-indikator dalam mengukur keberhasilan melaksanakan tugasnya secara pedagogik yang mencakup pemahaman landasan kependidikan, pemahaman terhadap peserta didik, pengembangan kurikulum, rancangan pembelajaran, pemanfaatan teknologi pembelaja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…With respect to the principal leadership, this study is confirmed by the results of Hasmayanti (2011) and Ginanjar et al, (2018b) asserting that the leadership of the principal affects the pedagogical competence of teachers. Principal leadership has a positive effect on the pedagogical competence of Islamic Education teachers to realize learning effectiveness (Ginanjar et al, 2018). Principal leadership has a linear relationship with teachers' pedagogical competence (Nellitawati & Boo, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the principal leadership, this study is confirmed by the results of Hasmayanti (2011) and Ginanjar et al, (2018b) asserting that the leadership of the principal affects the pedagogical competence of teachers. Principal leadership has a positive effect on the pedagogical competence of Islamic Education teachers to realize learning effectiveness (Ginanjar et al, 2018). Principal leadership has a linear relationship with teachers' pedagogical competence (Nellitawati & Boo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of madrasah principals' leadership also has a very strong effect (70.06%) on teachers' competence (Hasmayanti, 2011). The results of a study by Ginanjar et al, (2018) showed that there was a significant effect of principals' leadership on increasing the pedagogical competence of Islamic education teachers at SMPN 3 Karawang. Therefore, efforts are needed to improve taskoriented leadership (initiating structural) to increase the principals' leadership effectiveness variable so that it becomes better (Hasmayanti, 2011).…”
Section: Teachers' Pedagogical Competencementioning
confidence: 96%
See 1 more Smart Citation
“…Untuk mendukung terlaksananya tugas yang harus diemban oleh guru, perlu kompetensi yang harus dikuasai oleh guru sesuai dengan Undang-Undang sistem Pendidikan Nasional (Ginanjar & Assurur, 2018). Dalam Undang-Undang No.14 tahun 2005 pada pasal 10 ayat 1 dijelaskan bahwa "guru harus memiliki empat kompetensi dalam mengajar untuk menunjang pribadi guru agar menjadi guru yang profesional.…”
Section: A Pendahuluanunclassified
“…2 Ginanjar, M. H., Assurur, M., Wahidin, U., & Priyatna, M. (2018). Kepemimpinan Kepala Sekolah dan Pengaruhnya Terhadap Peningkatan Pedagogik Guru Pendidikan Agama Islam di SMP Negeri 3 Karawang Jawa Barat.…”
Section: E-issn: 2620-3839unclassified